Symmetry and monotonicity of positive solutions for a system involving fractional p&q-Laplacian in a ball. Issue 4 (3rd April 2023) - Cao, Linfen; Fan, Linlin
Abstract : In this paper, we study a nonlinear system involving the fractional p&q-Laplacian in the unit ball 1 ( − Δ ) p s 1 u ( x ) + ( − Δ ) q s 2 u ( x ) = u ( x ) ( v ( x ) ) β, x ∈ B 1 ( 0 ), ( − Δ ) p s 1 v ( x ) + ( − Δ ) q s 2 v ( x ) = v ( x ) ( u ( x ) ) α, x ∈ B 1 ( 0 )